Individual life horizon influences attitudes toward democracy - Marie Lechler; Uwe Sunde (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Support for democracy in the population is considered critical for the emergence and stability of democracy. Macro-determinants and retrospective experiences have been shown to affect the support for democracy at the individual level. We investigate whether and how the individual life horizon, in terms of the prospective length of life and age, affect individual attitudes toward democracy. Combining information from period life tables with individual survey response data spanning more than 260,000 observations from 93 countries over the period 1994-2014, we find evidence that the expected remaining years of life influence the attitudes toward a democratic political regime. The statistical identification decomposes the influence of age from the influence of the expected proximity to death. The evidence shows that support for democracy increases with age, but declines with expected proximity to death, implying that increasing longevity might help fostering the support for democracy. Increasing age while keeping the remaining years of life fixed as well as increasing remaining years of life for a given age group both contribute to the support for democracy.
Keywords: 330; attitudes toward democracy; life expectancy; aging